High sensitivity and selectivity triethylamine gas sensor based on ZnO–SmFeO3 molecular imprinted polymers. (May 2023) - Wang, Shutong; Xiong, Hao; Tang, Yunyang; Zhang, Weilong; Zhang, Yumin; Liu, Qingju; Zhang, Jin
Highlights: 3% ZnO-SmFeO3 molecular imprinted polymers (ZMIPs) were prepared by the sol-gel method combined with the molecular imprinting technique. 3% ZMIPs has a high sensitivity and selectivity properties to low concentration triethylamine gas, and the response to 5 ppm triethylamine reaches 150. Molecular imprinting technique enhances triethylamine gas sensing properties of 3%ZnO-SmFeO3 . Abstract: In this study, ZnO–SmFeO3 molecular imprinted polymers (ZMIPs) gas sensors for the detection of triethylamine (TEA) gas were successfully prepared via the sol–gel method combined with the molecular imprinting technique (MIT). The structure, morphology and chemical valence states of these materials were characterized via X-ray diffraction (XRD), scanning electron microscope (SEM), transmission electron microscopy (TEM), and X-ray photoelectron spectroscopy (XPS), and their gas-sensing properties and related mechanisms were studied. The results reveal that the ZMIPs consist of nanoparticles with a diameter of around 60 nm. 3% molar ratio (Zn: Sm=3: 97) of ZMIPs show an excellent sensitivity to TEA gas. At 200 °C, the response to 5 ppm of TEA gas reaches 150, and the response to other interferent gases is significantly lower than that to TEA gas. The 3% ZMIPs also show a good stability, a low detection limit of TEA gas and a good linear relationship between the response value and the concentration of TEA gas. The superior TEA gas-sensing performance of the 3% ZMIPs is attributed to the realization of specific identification sites and ZnO doping into ZMIPs. Composites are a promising TEA gas sensing material that can be used for a wide range of applications. Graphical abstract: Image, graphical abstract